Mutualistic coevolution and community diversity favour persistence in metacommunities under environmental changes. Issue 1990 (11th January 2023) - Cosmo, Leandro G.; Sales, Lilian P.; Guimarães, Paulo R.; Pires, Mathias M.
Abstract : Linking local to regional ecological and evolutionary processes is key to understand the response of Earth's biodiversity to environmental changes. Here we integrate evolution and mutualistic coevolution in a model of metacommunity dynamics and use numerical simulations to understand how coevolution can shape species distribution and persistence in landscapes varying in space and time. Our simulations show that coevolution and species richness can synergistically shape distribution patterns by increasing colonization and reducing extinction of populations in metacommunities. Although conflicting selective pressures emerging from mutualisms may increase mismatches with the local environment and the rate of local extinctions, coevolution increases trait matching among mutualists at the landscape scale, counteracting local maladaptation and favouring colonization and range expansions. Our results show that by facilitating colonization, coevolution can also buffer the effects of environmental changes, preventing species extinctions and the collapse of metacommunities. Our findings reveal the mechanisms whereby coevolution can favour persistence under environmental changes and highlight that these positive effects are greater in more diverse systems that retain landscape connectivity.